Human resource excellence : an assessment of strategies and trends - Lawler, Edward E., III; Boudreau, John W. (Stanford Business Books, an imprint of Stanford University Press, 2018)
The eighth version of this serial publication draws on twenty-one years of data collected by the Center for Effective Organizations to chart the state of the Human Resources--how it is organized and managed, how it contributes to organizational performance, and how it is changing. It provides an international benchmark against which to measure real-world practice.